Delayed Impacts of Spring Soil Moisture in the Tibetan Plateau on Early‐Summer Air Temperature in the Northern East Asia - Sang, Yinghan; Ren, Hong‐Li; Li, Mei (Geophysical research letters, 2025)
The northern East Asia (NEA) is suffering from significant temperature anomalies in recent years and the formation mechanisms remain unclear yet. With focus on non‐local effects of Tibetan Plateau soil moisture (TPSM), this study explores the close linkage between anomalies of TPSM in boreal spring and air temperature of NEA (NEAT) in early summer based on observational diagnosis, and the influence mechanism is verified by numerical model experiments. The drier mid‐west TPSM in April could persist into early summer and reduce the TP evaporation, which leads to positive anomalies of surface sensible heat flux heating the TP atmosphere. Heated air further exciting the wave train, and NEA is covered by positive geopotential height anomalies. Higher pressure results the downdraft and thus abnormally high air temperatures in NEA eventually. This study suggests that TPSM in spring may act as a new precursor providing an additional source of predictability for early‐summer NEAT. Plain Language Summary The northern East Asia (NEA) is suffering from significant temperature anomalies that cause extreme events like heat waves in recent years, and the inter‐annual prediction of temperature variations in NEA has become a key and hot issue. The correlation between summer air temperature in NEA (NEAT) and traditional factors such as sea surface temperature becomes unstable in recent years, which may result in low accuracy of inter‐annual prediction over this region. Therefore, the influences of other factors on NEAT are needed to be focused on. Based on the climatic effects of soil moisture, we show that soil moisture over the Tibetan Plateau (TPSM) in spring is significantly correlated with NEAT in early‐summer. By heating the atmosphere above TP, the negative TPSM signals persisting from April to June can excite the wave train from central Asia to NEA, and the positive geopotential height anomalies of which cover NEA. Higher pressure leads to the downdraft anomalies and thus abnormally high air temperatures in NEA. The results are verified by both observational analysis and numerical model experiments. This study suggests that TPSM in boreal spring may act as a new precursor providing an additional source of predictability for early summer NEAT. Key Points Soil moisture on Tibetan Plateau (Tibetan Plateau soil moisture (TPSM)) in spring is significantly correlated with early‐summer air temperature in northern East Asia TPSM anomalies persisting for 3 months from April to June affects surface heat fluxes and heats atmosphere above the plateau Heated atmosphere of TP excites the wave train that NEA is covered by positive geopotential height anomalies benefiting higher temperature